Digital Divide and Older People: Thoughts from the Professionals in Peñalolén (Santiago, Chile); [Brecha Digital y Personas Mayores: Miradas de Las y Los Profesionales en Peñalolén (Santiago, Chile)] - Bravo-Rojas, C (Pontificia Universidad Catolica de Chile, 2025)
In the digital world, only some people can participate actively. Older people in situations of vulnerability or social exclusion are often out of this world. In fact, in the Latin American context, the digital divide increases in this age group. In this research, using an intended sample, 23 professionals who work daily with older people in Peñalolén (Santiago, Chile) were interviewed. The main objective was to identify their vision of how the ageing population lives through the digital divide in a period shaped by the COVID-19 pandemic. Among the results, the professionals highlight difficulties and achievements associated with this gap, related to (a) connectivity, linked not only to Internet access, but also derived from intergenerational conflicts that are generated in the private sphere; (b) digitalization, and access to municipal services, related to local and national government efforts, and (c) digital literacy. In conclusion, the authors thematize the inequalities related to the digital divide and reflect on the limitations and proposals for future research. © 2023 by Psykhe